Dental Implants and Oral Lichen Planus: Review and Protocol - Torrejon-Moya , Aina; Saka-Herrán, Constanza; Izquierdo-Gómez, Keila; Roig, Antoni Marí; Estrugo-Devesa, Albert; López, José López (New Advances in Medicine and Medical Science Vol. 1, 2023)
Oral lichen planus [OLP] is an autoimmune and chronic inflammatory disease. The aetiology of OLP is still unknown, but it is believed to be associated with cell-mediated immune dysregulation at the level of the basal membrane. Since OLP is a mucosal disease, it has been suggested to affect the ability of attachment to the titanium surface; and although some conditions are considered as risk factors for dental implants, there are only a few absolute contraindications for this rehabilitation option. Our aim is to present a systematic review that answers the PICO question: rehabilitation with dental implants in patients with OLP is a valid treatment option with a high survival rate. The survival of 93,88% rate obtinned is similar to the survival rate of implant rehabilitation in patients without any pathology or systemic condition, which is 92% or 95%, depending on the prosthetic rehabilitation. In order to maintain this high survival rate, frequent follow-up appointments and oral hygiene instructions should be established to eliminate inflammatory tissue response (peri-implant mucositis and peri-implantitis). According to the SORT criteria, level A can be established to conclude that OLP patients can be rehabilitated with dental implants.